Job satisfaction among physical and sports activity instructors for people with special needs - BOURAGdA, Mohammed; Ababsa, Nadjibe; himoud, ahmed; kheri, Said (sports creativity, 2025)
The study of job satisfaction has been of great interest to industrial and organizational psychologists since its inception in the early 1930s, following the well-known Hawthorne studies (1927-1932) conducted by Elton Mayo. Workers' rights to health, psychological, and social care, as well as annual leave, began to be recognized, and efforts were made to reduce weekly working hours to 40 hours. Supervisors were also trained to treat workers well in order to boost their morale. These experiments played an important role in the emergence of the human relations school as a reaction to the ideas and principles of the scientific management movement. All of these studies dealt with job satisfaction in the industrial and administrative sectors and did not include all categories of workers, especially those engaged in physical and athletic activities. Furthermore, these studies did not address the category of people with special needs, despite their role and status in society, which led us to conduct this research, which examines the job satisfaction of physical and athletic activity supervisors for people with special needs. The research sample included 115 physical and sports activity supervisors for people with special needs. Through this study, we found that supervisors were dissatisfied with their working conditions, pay, promotion opportunities, colleagues, and supervision.